2020
DOI: 10.1128/mbio.00209-20
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Hidden Pathogens: Cell-Penetrating Enzybiotics Eradicate Intracellular Drug-Resistant Staphylococcus aureus

Abstract: Staphylococcus aureus is a major concern in human health care, mostly due to the increasing prevalence of antibiotic resistance. Intracellular localization of S. aureus plays a key role in recurrent infections by protecting the pathogens from antibiotics and immune responses. Peptidoglycan hydrolases (PGHs) are highly specific bactericidal enzymes active against both drug-sensitive and -resistant bacteria. However, PGHs able to effectively target intracellular S. aureus are not yet available. To overcome this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 77 publications
1
61
0
Order By: Relevance
“…To identify PGH constructs featuring high antibacterial activity against S. aureus in human serum, we first modified a previously established protocol ( 50 ) to screen a comprehensive collection of more than 300 parental and engineered staphylococcal PGHs. This procedure has previously been successfully applied to identify lytic enzymes highly active in milk ( 50 ) and under intracellular conditions ( 51 ) and was adapted here for human serum. Applying this protocol in an iterative fashion, using S. aureus Newman as a target strain, enabled us to narrow down the selection of possible candidates to the 25 most promising constructs (PGH-1 to PGH-25; see Table S1 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…To identify PGH constructs featuring high antibacterial activity against S. aureus in human serum, we first modified a previously established protocol ( 50 ) to screen a comprehensive collection of more than 300 parental and engineered staphylococcal PGHs. This procedure has previously been successfully applied to identify lytic enzymes highly active in milk ( 50 ) and under intracellular conditions ( 51 ) and was adapted here for human serum. Applying this protocol in an iterative fashion, using S. aureus Newman as a target strain, enabled us to narrow down the selection of possible candidates to the 25 most promising constructs (PGH-1 to PGH-25; see Table S1 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…Then, N-terminal fusions of the seven most active lysins to six different CPPs were prepared. Whereas all JDlys-CPP fusions were inactive in the study of Wang, lysin-CPP combinations retained antibacterial activity in the work of R€ ohrig and colleagues (Wang et al 2018;R€ ohrig et al 2020). They also observed that the trans-activating transcription factor of HIV type 1 (Tat) has the least detrimental effect on the in vitro antibacterial activity.…”
Section: ;mentioning
confidence: 99%
“…Another example is the fusion with cell-penetrating peptides (CPPs). Here, the reduction in antibacterial activity was compensated by targeting intracellular S. aureus thereby eradicating a major cause of recurrent, chronic infections (Wang et al 2018;R€ ohrig et al 2020).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although agents with dual antimicrobial and anti-tumor activities would be ideal, combined applications of mono-therapeutic agents may easily provide the same effect. Two types of agents to be considered in this class are bacteriophages [184][185][186][187] and enzybiotics [188][189][190][191], which have attracted substantial attention in recent times, and can be used in prophylactic and therapeutic applications in antimicrobial and anticancer protocols. Bacteriophages have been engineered for medical applications [192] in ways allowing them to retain their antibacterial activity [185] and have been used as anticancer drug delivery systems [186,192], their possible effects on anti-tumor immunity and the response to anticancer therapy must be further evaluated.…”
Section: Alternative Approachesmentioning
confidence: 99%